2017
DOI: 10.1159/000459688
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography in Diabetic Maculopathy

Abstract: Fluorescein angiography (FA) and indocyanine green angiography have provided information about the normal retinal and choroidal anatomy, nearly comparable to histological findings. These tests have been fundamental in the evaluation of all retinal and choroidal vascular diseases and have allowed clinicians to define and diagnose several pathological conditions. FA became the "gold standard" in retinal imaging due to the capacity to visualize the retinal capillary bed and its changes, both in the macular area a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
14
0
3
Order By: Relevance
“…that DR severity and BCVA were significantly correlated with SCP-VD rather than DCP-VD. [27][28][29][30][31][32][33][34][35][36] We found a significant negative correlation between the BCVA (LogMAR) and vessel density in both DCP and SCP. Our results are comparable to a study by Samara et al; 25 however, no correlation was found between them in another study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…that DR severity and BCVA were significantly correlated with SCP-VD rather than DCP-VD. [27][28][29][30][31][32][33][34][35][36] We found a significant negative correlation between the BCVA (LogMAR) and vessel density in both DCP and SCP. Our results are comparable to a study by Samara et al; 25 however, no correlation was found between them in another study.…”
Section: Discussionmentioning
confidence: 50%
“…Macular ischemia (inadequate blood supply) may contribute to both macular dysfunction and poor visual acuity. 4 Past studies concluded that diminished vessel density, irregularity of the FAZ and increased FAZ area were associated with progression and worsening of DR. 24,31,32 Other studies also reported that poorer visual acuity was correlated with diminished vessel density and widening of the FAZ area in DR patients without diabetic macular edema. 25 In a 2019 study, Hsiao et al 15 concluded that poor visual acuity in diabetic maculopathy was significantly correlated with decreased DCP-VD, and no correlation was found with SCP-VD.…”
Section: Discussionmentioning
confidence: 95%
“…Introducing OCTA as an alternative imaging modality may alleviate the need for FA in many cases. [ 5 91 92 ]…”
Section: Resultsmentioning
confidence: 99%
“…Optical coherence tomography angiography is a novel diagnostic tool that can potentially impact ocular medical therapies in the future. It has been tried as an early diagnostic and assessment tool for age-related macular degeneration (AMD) [ 21 24 ], as a research tool in order to improve the current understanding of ischemic diseases that affects the different layers of the retinal microcirculation (diabetic retinopathy) [ 25 , 26 ], cotton wool spots, acute macular neuroretinopathy, paracentral acute middle maculopathy, and macular telangiectasia type 2 among others [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%